2006
DOI: 10.1016/j.psychres.2005.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Light exposure is related to social and emotional functioning and to quality of life in older women

Abstract: While there are data supporting the use of light in clinical populations, there has been less investigation of relationships among light and psychological variables in non-clinical samples. Subjects were 459 ethnically diverse women (mean age 67.68) recruited as part of the Women's Health Initiative. Light exposure and sleep were measured with an Actillume wrist actigraph. Subjects completed questionnaires, investigating Social Support, Social Functioning, Social Strain, Quality of Life, Satisfaction with Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…These studies included a cohort of 450 post menopausal women from the Womens Health Initiative study to evaluate how depression (using the Center for Epidemiologic Studies Depression scale [CESD]) was linked to light exposure as measured by wrist actigraphy with a light meter. 20,37 Fewer depressive symptoms were associated with higher levels of light exposure (p<0.05), but this relationship could be driven by other factors associated with quality of life. 20 In another study, utilizing the same cohort, an investigation into mood and light exposure showed a modest, non-significant correlation between environmental light and depressive symptoms.…”
Section: Exposure Measured Using Actigraphy (N=2)mentioning
confidence: 94%
See 4 more Smart Citations
“…These studies included a cohort of 450 post menopausal women from the Womens Health Initiative study to evaluate how depression (using the Center for Epidemiologic Studies Depression scale [CESD]) was linked to light exposure as measured by wrist actigraphy with a light meter. 20,37 Fewer depressive symptoms were associated with higher levels of light exposure (p<0.05), but this relationship could be driven by other factors associated with quality of life. 20 In another study, utilizing the same cohort, an investigation into mood and light exposure showed a modest, non-significant correlation between environmental light and depressive symptoms.…”
Section: Exposure Measured Using Actigraphy (N=2)mentioning
confidence: 94%
“…The studies evaluated different aspects of psychosocial well-being including behavioral disturbances (n=3), 11,35,38 20 and the Perceived Quality of Life Scale. 39 Significant results will be reported (p value) and non-significant results will be referred to as NS.…”
Section: Outcome Assessmentmentioning
confidence: 99%
See 3 more Smart Citations